Konsep Perancangan Adaptif pada GOR Saparua Bandung: Dialog antara Preservasi Nilai Sejarah, Kebutuhan Moderen dan Fungsional - Manda, Christianto Cornelius Raja; Herwindo, Rahadhian Prajudi (Universitas Muhammadiyah Palembang, 2026)
Saparua Sports Hall in Bandung, a type C cultural heritage building designed in the Jengki architectural style, faces a challenge between the preservation of its historical value and the demands of moderen functionality. The building possesses significant historical and architectural merit, particularly its wooden façade, yet its spatial layout and facilities no longer meet contemporary standards. This research aims to formulate an adaptive design concept that bridges these two aspects through a qualitative approach and a case study. The result is a concept centered on a